A strontium ion-loaded polyether ether ketone composite material, a preparation method and application thereof

CN122516456BActive Publication Date: 2026-10-23JILIN UNIVERSITY
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202610996954.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-07-06
Publication Date
2026-10-23
Estimated Expiration
2046-07-06

AI Technical Summary

Technical Problem

PEEK在力学性能上非常适用于承重植入应用,但其生物惰性表面缺乏主动调节骨质疏松症病理免疫微环境的能力

Benefits of technology

1、本发明使用羧甲基壳聚糖稳定的无定形碳酸锶,解决“高活性与稳定性”的矛盾。利用羧甲基壳聚糖分子上的丰富羧基(-COO-)与无定形碳酸锶表面的锶离子形成配位络合,空间稳定无定形碳酸锶纳米颗粒,抑制其结晶转化,使其在矿化过程中保持无定形状态。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122516456B_ABST
    Figure CN122516456B_ABST
Patent Text Reader

Abstract

The application discloses a kind of strontium ion loaded polyether ether ketone composite material and its preparation method and application, and belongs to the technical field of biomedical materials, wherein, the preparation method of polyether ether ketone composite material includes the following steps: preparation carboxymethyl chitosan stabilized amorphous strontium carbonate nano composite solution;Preparation strontium ion loaded self-assembled mineralized collagen solution;Surface nitration treatment is carried out to base material, and is reduced to amino, and the base material with amino on surface is obtained;Glutaraldehyde is used to activate the base material with amino on surface, and the glutaraldehyde modified base material is obtained;Glutaraldehyde modified base material and strontium ion loaded self-assembled mineralized collagen solution are co-incubated, covalent fixation is realized, and strontium ion loaded polyether ether ketone composite material is obtained.The strontium ion is loaded on base material in the application, can respond to pH and release drug, significantly enhance its biological activity and osteogenic integration ability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of biomedical materials technology, specifically to a strontium-loaded polyetheretherketone composite material, its preparation method, and its application. Background Technology

[0002] The clinical application of polyetheretherketone (PEEK) remains limited by its insufficient interfacial biological properties. PEEK-based materials lack active functional groups on their surface and typically exhibit hydrophobicity and bioinertness, which hinders early protein adsorption, cell adhesion, and subsequent osteogenic differentiation, thereby weakening the osseointegration effect between the implant and the host bone. To address this issue, various modification approaches have been proposed, including material composites, surface treatments, surface coatings, physical modification, and chemical functionalization. Among these, chemical modification has attracted widespread attention due to its ability to introduce reactive sites on the material surface and further immobilize bioactive components. However, overall, existing modification strategies still have room for improvement in promoting long-term stable osseointegration. Therefore, developing PEEK composite materials that combine mechanical adaptability with high bioactivity remains of significant research importance.

[0003] Mounting evidence suggests that the healing process of osteoporotic bone defects is regulated by bone immune dysregulation, rather than simply by material-cell incompatibility. An acidic environment and inflammatory signals encourage macrophages to differentiate into pro-inflammatory and pro-bone-resorption phenotypes and increase the secretion of osteoclastogenic mediators. While PEEK is mechanically well-suited for load-bearing implants, its bioinert surface lacks the ability to actively modulate the pathoimmune microenvironment of osteoporosis. Therefore, implantation interfaces capable of sensing local acidity and translating it into local bone immune regulatory signals are of significant practical value. Summary of the Invention

[0004] The purpose of this invention is to provide a strontium-loaded polyetheretherketone composite material, its preparation method, and its application, in order to solve the problems mentioned in the background art.

[0005] To achieve the above objectives, the present invention provides the following technical solution: A method for preparing a strontium-loaded polyetheretherketone composite material includes the following steps: In the presence of chitosan, strontium ions react with carbonate ions in a liquid phase system to obtain a chitosan-stable amorphous strontium carbonate nanocomposite solution. Amorphous strontium carbonate nanocomposite solution was mixed with collagen solution, and collagen self-assembly and mineralization were promoted by dialysis and pH adjustment to obtain a strontium-loaded self-assembled mineralized collagen solution. Polyether ether ketone (PEEK) material was used as the matrix material and subjected to surface nitration treatment to obtain a matrix material with nitro groups on the surface. The nitro groups in the matrix material with nitro groups on the surface are reduced to amino groups to obtain a matrix material with amino groups on the surface. Glutaraldehyde was used to activate a matrix material with amino groups on its surface to obtain a glutaraldehyde-modified matrix material. Glutaraldehyde-modified matrix material was co-incubated with a strontium-loaded self-assembled mineralized collagen solution to achieve covalent fixation, resulting in a strontium-loaded polyether ether ketone composite material.

[0006] Furthermore, the step of reacting strontium ions with carbonate ions in a liquid phase system in the presence of chitosan to obtain a chitosan-stable amorphous strontium carbonate nanocomposite solution specifically includes: Chitosan was dissolved in deionized water at a mass concentration of 1.0% to 3.0%, and then the pH value was adjusted to 2 to 5 to obtain a chitosan solution. Strontium salt was prepared into an aqueous solution with a mass concentration of 8% to 20%, and added dropwise to the chitosan solution under stirring; then carbonate equivalent to 1% to 4% of the mass of strontium salt was added to obtain a chitosan-stable amorphous strontium carbonate nanocomposite solution; the mass ratio of chitosan to strontium salt was (0.3-0.4):(0.9-1).

[0007] Furthermore, the chitosan is carboxymethyl chitosan; the strontium salt is strontium chloride hexahydrate; and the carbonate is sodium carbonate.

[0008] Further, the steps of mixing an amorphous strontium carbonate nanocomposite solution with a collagen solution and promoting collagen self-assembly and mineralization through dialysis and pH adjustment to obtain a strontium-loaded self-assembled mineralized collagen solution specifically include: Amorphous strontium carbonate nanocomposite solution and acid-dissolved collagen solution were mixed at a volume ratio of (2-4):1, and then dialyzed in phosphate buffer solution. The phosphate buffer solution was changed periodically until the pH value changed to 5.0~7.0 to obtain a mixed system. Add 0.5-1.5 mol / L alkaline solution to the mixed system to adjust the pH to 7.0-8.0 to promote the conversion of amorphous minerals. Then transfer to HEPES buffer for dialysis to obtain a strontium-loaded self-assembled mineralized collagen solution; wherein the collagen is type I collagen; the volume of HEPES buffer is 100%-300% of the volume of the mixed system.

[0009] Further, the step of using polyetheretherketone (PEEK) material as the matrix material and performing surface nitration treatment to obtain a matrix material with nitro groups on the surface specifically includes: The matrix material was ultrasonically cleaned sequentially with acetone, ethanol and distilled water, and then vacuum dried to obtain the pretreated matrix material. The pretreated matrix material is immersed in a concentrated nitric acid solution with a mass concentration of 60%~75% and stirred. Then, it is ultrasonically cleaned to remove residual nitric acid and then vacuum dried to obtain a matrix material with nitro groups on the surface.

[0010] Further, the step of reducing the nitro groups in the matrix material with nitro groups on the surface to amino groups to obtain a matrix material with amino groups on the surface specifically includes: A matrix material with nitro groups on its surface was mixed with palladium on carbon and hydrazine hydrate, and anhydrous ethanol was used as a solvent to prepare a reduction reaction system. The system was refluxed at 90-110°C under a protective atmosphere. The volume fraction of hydrazine hydrate in the reduction reaction system was 10%-30%. After the reaction was completed, the material was ultrasonically cleaned to remove unreacted substances and then dried to obtain a matrix material with amino groups on its surface.

[0011] Further, the step of activating the matrix material with amino groups on its surface using glutaraldehyde to obtain the glutaraldehyde-modified matrix material specifically includes: The matrix material with amino groups on its surface is immersed in a glutaraldehyde aqueous solution with a volume fraction of 1% to 2.5% to activate the amino groups on the surface and introduce active aldehyde groups. It is then rinsed to remove unreacted glutaraldehyde, thus obtaining a glutaraldehyde-modified matrix material.

[0012] Furthermore, after covalent fixation, the following steps are also included: The solution is used for sealing with a glutamic acid solution; the concentration of the glutamic acid solution is 0.1~0.9 mol / L.

[0013] Another object of the present invention is to provide a strontium-loaded polyether ether ketone composite material prepared by the above-described preparation method.

[0014] Another object of the present invention is to provide the application of the above-mentioned strontium-loaded polyetheretherketone composite material in the preparation of bone graft materials, and / or bone fixation materials, and / or bone repair materials.

[0015] This invention provides a method for preparing a strontium-loaded polyetheretherketone composite material. By loading strontium ions onto a matrix material, the material can release drugs in response to pH, significantly enhancing its bioactivity and osteogenic integration capacity. Compared with existing technologies, this invention has the following beneficial technical effects: 1. This invention uses carboxymethyl chitosan-stabilized amorphous strontium carbonate to resolve the contradiction between "high activity and stability." It utilizes the abundant carboxyl groups (-COO) on the carboxymethyl chitosan molecule. - It forms a coordination complex with strontium ions on the surface of amorphous strontium carbonate, spatially stabilizing the amorphous strontium carbonate nanoparticles, inhibiting their crystallization transformation, and keeping them in an amorphous state during the mineralization process.

[0016] 2. This invention constructs a mineralized collagen functional layer loaded with strontium ions on the surface of a matrix material and achieves an organic-inorganic composite structure through a simultaneous self-assembly / mineralization strategy. During the collagen self-assembly to form fibers, a carboxymethyl chitosan-stabilized amorphous strontium carbonate precursor is simultaneously introduced, allowing strontium carbonate nanoclusters to be deposited in situ and uniformly within the gaps and interiors of collagen fibers, forming a highly biomimetic organic-inorganic composite structure. This method effectively improves the bioinertness of the matrix material surface and enhances the affinity of the material surface for cells, thereby promoting cell adhesion, expansion, proliferation, and osteogenic differentiation, and improving the interfacial osteointegration capacity of the implant material.

[0017] 3. The strontium-loaded polyetheretherketone composite material prepared by this invention exhibits pH-responsive characteristics, and can enhance Sr under acidic conditions. 2+ This invention enables on-demand release of strontium into the pathological microenvironment. It utilizes the weakened coordination effect caused by the carboxyl protonation of carboxymethyl chitosan, coupled with the accelerated decomposition of amorphous strontium carbonate under acidic conditions. These two factors synergistically trigger the release of strontium from the pathological microenvironment. 2+ It accelerates the release of strontium. It can serve as an acid-responsive strontium release interface for the acidic microenvironment of osteoporosis, enabling intelligent bone repair that integrates on-demand strontium release from the pathological microenvironment, immune regulation, and bone integration.

[0018] 4. This invention employs a combination of surface chemical grafting (chemical activation of the matrix material surface) and covalent fixation of the mineralized collagen functional layer to stably introduce a strontium-loaded mineralized collagen functional layer onto the surface of a bioinert matrix material. This covalent fixation method not only ensures the long-term stability of the mineralized collagen functional layer under physiological and mechanical conditions but also does not impair the response sensitivity of the collagen layer. Even under covalent constraint, carboxymethyl chitosan can still sense pH changes and undergo conformational / charge state alterations, which are then transmitted to the macroscopic Sr. 2+ Release. Moreover, this modification method mainly acts on the surface layer of the material, which can improve the surface biological properties with minimal impact on the main mechanical properties of the matrix.

[0019] 5. The preparation method provided by this invention has clear process steps, relatively mild reaction conditions, readily available raw materials and equipment, and good controllability and repeatability of the operation process, making it easy to implement in the laboratory and scale up the subsequent process, thus having good practical application value. Attached Figure Description

[0020] Figure 1 This is a schematic flowchart illustrating a method for preparing a strontium-loaded polyetheretherketone composite material according to an embodiment of the present invention; in the figure, a is a schematic flowchart of the preparation process of self-assembled mineralized collagen loaded with strontium ions; b is a schematic flowchart of the preparation process of the strontium-loaded polyetheretherketone composite material; CMC represents carboxymethyl chitosan; Sr 2+Strontium ions are represented by strontium; ASC represents amorphous strontium carbonate; CMA / ASC represents a carboxymethyl chitosan-stabilized amorphous strontium carbonate nanocomposite solution; SSMC represents self-assembled mineralized collagen loaded with strontium ions; NP represents polyetheretherketone (PEEK) materials with nitro groups on the surface; AP represents PEEK materials with amino groups on the surface; GP represents glutaraldehyde-modified PEEK materials; GP-SSMC represents PEEK composite materials loaded with strontium ions.

[0021] Figure 2 This is a schematic diagram of a transmission electron microscope (TEM) of the strontium-loaded self-assembled mineralized collagen prepared in Example 1.

[0022] Figure 3 The images show the surface XPS spectra of samples from different processing stages in Example 1.

[0023] Figure 4 This is a comparison diagram of the surface hydrophilicity of samples at different treatment stages in Example 1.

[0024] Figure 5 The graph shows the strontium ion sustained-release curves of the strontium-loaded polyetheretherketone composite material prepared in Example 1 under different pH conditions.

[0025] Figure 6 This is a comparison of the Raw264.7 cell proliferation experiment results of samples from different treatment stages in Example 1.

[0026] Figure 7 This is a comparison of the alkaline phosphatase (ALP) expression results of rBMSCs in samples from different treatment stages in Example 1. Detailed Implementation

[0027] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0028] In one embodiment of the present invention, a method for preparing a polyetheretherketone composite material loaded with strontium ions is provided, comprising the following steps: S1. Weigh 0.3-0.4 g of chitosan (such as carboxymethyl chitosan or other derivatives) and dissolve it in deionized water at a mass concentration of 1.0%-3.0%. Stir magnetically at room temperature until completely dissolved. Then adjust the pH value to 2-5 with an acidic solution such as hydrochloric acid to obtain a chitosan solution. Separately weigh 0.9-1 g of strontium salt (such as strontium chloride hexahydrate) and dissolve it in 8 mL of deionized water. Add the solution dropwise to the chitosan solution while stirring. Then add 0.009-0.04 g of carbonate (such as sodium carbonate) dropwise and continue stirring for 20-40 min to obtain a chitosan-stable amorphous strontium carbonate nanocomposite solution.

[0029] S2. The above amorphous strontium carbonate nanocomposite solution and type I collagen solution dissolved in 10 mg / ml acetic acid were added to the dialysis bag at a volume ratio of (2-4):1 to obtain a 7.5 mL mixture. The mixture was then dialyzed in phosphate buffer, with the phosphate buffer being replaced every 20-28 h until the pH of the system in the bag reached 5.0-7.0. Subsequently, 0.5-1.5 mol / L alkaline solution (such as sodium hydroxide solution) was added dropwise to adjust the pH to 7.0-8.0. The dialysis bag was then transferred to 7.5-22.5 mL of HEPES buffer and dialyzed for another 2-4 days to obtain a strontium-loaded self-assembled mineralized collagen solution.

[0030] S3. The matrix material (such as polyetherketone material, polyetheretherketone material, polyetheretherketone material, etc., polyaryletherketone material, in this embodiment of the invention, polyetheretherketone material is used as an example, but it can also be replaced with other polyaryletherketone materials) is ultrasonically cleaned with acetone, ethanol and distilled water for 5-15 min each, vacuum dried and then immersed in nitric acid with a mass concentration of 60%-75%, and stirred and reacted at room temperature for 12-36 h; after the reaction is completed, it is ultrasonically cleaned with distilled water until neutral, and then vacuum dried to obtain a matrix material with nitro groups on the surface.

[0031] S4. Mix the nitro-coated matrix material with 0.22–0.30 g palladium on carbon and 3.5–13.5 mL of hydrazine hydrate (80%–85% by mass), and reflux at 90–110 °C for 5–7 h under nitrogen protection, using 35–45 mL of anhydrous ethanol as solvent. After the reaction, ultrasonically clean the mixture with ethanol and distilled water for 5–15 min each, and dry it at 30–50 °C to obtain the amino-coated matrix material.

[0032] S5. Place the matrix material with amino groups on the surface in a glutaraldehyde aqueous solution with a volume fraction of 1.0~3.0% and soak it at room temperature for 3~5 h to activate the amino groups on the surface and introduce active aldehyde groups; then rinse thoroughly with deionized water 1~5 times to obtain the glutaraldehyde-modified matrix material.

[0033] S6. The glutaraldehyde-modified matrix material was co-incubated with 6–10 mL of strontium-loaded self-assembled mineralized collagen solution at 3–5 °C for 10–14 h to achieve covalent fixation on the surface. After incubation, the sample was gently rinsed with deionized water to remove physically adsorbed substances, and then blocked with 0.1–0.9 mol / L glutamic acid solution for 1–3 h to reduce the potential cytotoxicity of free aldehyde groups, thus obtaining the strontium-loaded polyetheretherketone composite material.

[0034] In this embodiment of the invention, type I collagen, one of the main organic components in the extracellular matrix of natural bone tissue, plays an important role in bone matrix formation and mineralization. Mineralized collagen systems constructed based on collagen fibers are closer to natural bone tissue in composition and microstructure, and contribute to the formation of a more suitable osteogenic microenvironment. Introducing collagen fibers or mineralized collagen onto the surface of polyetheretherketone (PEEK) materials is expected to improve the bioinertness of the material surface and enhance the interfacial interaction between the implant and surrounding bone tissue.

[0035] As a trace element related to bone metabolism, strontium ions at appropriate levels can promote the adhesion, proliferation and osteogenic differentiation of osteoblast-related cells. Furthermore, by regulating the bone immune microenvironment, strontium ions can promote the transformation of macrophages into anti-inflammatory phenotypes that are conducive to tissue repair, thereby enhancing the osteogenic differentiation capacity of materials.

[0036] Chitosan and its derivatives are widely available, possess excellent biocompatibility, low toxicity, and modifiability, and are widely used in bone tissue engineering and biomedical materials. Among them, carboxymethyl chitosan has particularly significant advantages: its ionizable carboxyl groups can stabilize amorphous mineral precursors and may impart pH-responsive hydration and ion release properties to the interface; at the same time, its simultaneous self-assembly / mineralization process provides a feasible pathway for integrating bioactive ions into the collagen matrix.

[0037] Unless otherwise specified, all raw materials used in the following embodiments are commercially available products and can be purchased through commercial channels. The invention will be described in detail below through specific embodiments in practical applications.

[0038] Example 1: As Figure 1 As shown, this embodiment provides a method for preparing a polyetheretherketone composite material loaded with strontium ions, specifically including the following steps: S1. Weigh 0.35 g of carboxymethyl chitosan (CMC) powder and add it to 20 mL of deionized water. Stir magnetically at room temperature until completely dissolved. Adjust the pH of the solution to 3.5 with 1 mol / L hydrochloric acid. Separately, weigh 0.95 g of strontium chloride hexahydrate and dissolve it in 8 mL of deionized water. Add the solution dropwise to the carboxymethyl chitosan solution while stirring. Then add 0.02 g of sodium carbonate dropwise and continue stirring for 30 min to obtain a carboxymethyl chitosan-stabilized amorphous strontium carbonate (ASC) nanocomposite solution (named CMC / ASC).

[0039] S2. The above amorphous strontium carbonate nanocomposite solution and type I collagen solution dissolved in 10 mg / ml acetic acid were added to the dialysis bag at a volume ratio of 3:1 to obtain a 7.5 mL mixture. The mixture was then dialyzed in phosphate buffer, with the phosphate buffer changed every 24 h, until the pH of the system in the bag reached 6.0. Subsequently, 1 mol / L sodium hydroxide was added dropwise to adjust the pH to 7.4. The dialysis bag was then transferred to 15 mL of HEPES buffer and dialyzed for another 3 days to obtain strontium-loaded ions (Sr). 2+ A self-assembled mineralized collagen solution (named SSMC).

[0040] S3. The polyether ether ketone (PEEK) material was ultrasonically cleaned with acetone, ethanol and distilled water for 10 min each, vacuum dried and then immersed in 68% nitric acid. The mixture was stirred and reacted at room temperature for 24 h. After the reaction was completed, the material was ultrasonically cleaned with distilled water until neutral and then vacuum dried to obtain the surface-nitrated polyether ether ketone material (named NP).

[0041] S4. Mix 2.0 g NP with 0.25 g palladium on carbon and 10 mL of 80% hydrazine hydrate, and reflux at 100 °C for 6 h under nitrogen protection using 40 mL anhydrous ethanol as solvent. After the reaction is complete, ultrasonically clean with ethanol and distilled water for 10 min each, and dry at 40 °C to obtain a polyether ether ketone material with amino groups on the surface (named AP).

[0042] S5. Place 2.0 g AP in a 2.0% (v / v) glutaraldehyde aqueous solution and soak at room temperature for 4 h to activate the amino groups on the surface and introduce active aldehyde groups; then rinse thoroughly with deionized water 3 times to obtain glutaraldehyde-modified polyether ether ketone material (named GP).

[0043] S6. 2.0 g GP and 8 mL of strontium-loaded self-assembled mineralized collagen solution were co-incubated at 4 °C for 12 h to achieve covalent fixation on the surface. After incubation, the sample was gently rinsed with deionized water to remove physically adsorbed substances, and then blocked with 0.50 mol / L glutamic acid solution for 2 h to obtain the strontium-loaded polyetheretherketone composite material (named GP-SSMC).

[0044] Example 2: This example provides a method for preparing a polyetheretherketone composite material loaded with strontium ions, specifically including the following steps: S1. Weigh 0.30 g of carboxymethyl chitosan powder and add it to 20 mL of deionized water. Stir magnetically at room temperature until completely dissolved. Adjust the pH of the solution to 3.0 with 1 mol / L hydrochloric acid. Separately, weigh 0.90 g of strontium chloride hexahydrate and dissolve it in 6 mL of deionized water. Add this solution dropwise to the carboxymethyl chitosan solution while stirring. Then, add 0.015 g of sodium carbonate dropwise and continue stirring for 30 min to obtain a carboxymethyl chitosan-stabilized amorphous strontium carbonate nanocomposite solution (CMC / ASC).

[0045] S2. The above amorphous strontium carbonate nanocomposite solution and type I collagen solution dissolved in 10 mg / ml acetic acid were added to the dialysis bag at a volume ratio of 3:1 to obtain a 7.5 mL mixture. The mixture was then dialyzed in phosphate buffer, with the phosphate buffer replaced every 24 h, until the pH of the system in the bag reached 5.8. Subsequently, 1 mol / L sodium hydroxide was added dropwise to adjust the pH to 7.2. The dialysis bag was then transferred to 7.5 mL of HEPES buffer and dialyzed for another 2 days to obtain a strontium-loaded self-assembled mineralized collagen solution (SSMC).

[0046] S3. The PEEK material was ultrasonically cleaned with acetone, ethanol and distilled water for 10 min each, vacuum dried and then immersed in 65% nitric acid. The mixture was stirred and reacted at room temperature for 18 h. After the reaction was completed, the material was ultrasonically cleaned with distilled water until neutral and then vacuum dried to obtain a polyether ether ketone material with nitro groups on the surface (named NP-2).

[0047] S4. Mix 2.0 g NP-2 with 0.22 g palladium on carbon and 8 mL of 80% hydrazine hydrate, and reflux at 95 °C for 5 h under nitrogen protection using 35 mL anhydrous ethanol as solvent. After the reaction is complete, ultrasonically clean with ethanol and distilled water for 10 min each, and dry at 40 °C to obtain a polyetheretherketone material with amino groups on the surface (named AP-2).

[0048] S5. Place 2.0 g AP-2 in a 1.5% (v / v) glutaraldehyde aqueous solution and soak at room temperature for 4 h. Then rinse thoroughly with deionized water 3 times to obtain glutaraldehyde-modified polyether ether ketone material (named GP-2).

[0049] S6. 2.0 g GP-2 and 6 mL of strontium-loaded self-assembled mineralized collagen solution were co-incubated at 4 °C for 12 h. After incubation, the mixture was gently rinsed with deionized water and then blocked with 0.30 mol / L glutamic acid solution for 2 h to obtain strontium-loaded polyetheretherketone composite material (named GP-SSMC-2).

[0050] Example 3: This example provides a method for preparing a polyetheretherketone composite material loaded with strontium ions, specifically including the following steps: S1. Weigh 0.40 g of carboxymethyl chitosan powder and add it to 20 mL of deionized water. Stir magnetically at room temperature until completely dissolved. Adjust the pH of the solution to 4.0 with 1 mol / L hydrochloric acid. Separately, weigh 1.00 g of strontium chloride hexahydrate and dissolve it in 10 mL of deionized water. Add the solution dropwise to the carboxymethyl chitosan solution while stirring. Then add 0.025 g of sodium carbonate dropwise and continue stirring for 30 min to obtain a carboxymethyl chitosan-stabilized amorphous strontium carbonate nanocomposite solution (CMC / ASC).

[0051] S2. The above amorphous strontium carbonate nanocomposite solution and type I collagen solution dissolved in 10 mg / ml acetic acid were added to the dialysis bag at a volume ratio of 3:1 to obtain a 7.5 mL mixture. The mixture was then dialyzed in phosphate buffer, with the buffer changed every 24 h, until the pH of the system in the bag reached 6.5. Subsequently, 1 mol / L sodium hydroxide was added dropwise to adjust the pH to 7.8. The dialysis bag was then transferred to 22.5 mL of HEPES buffer and dialyzed for another 5 days to obtain a strontium-loaded self-assembled mineralized collagen solution (SSMC).

[0052] S3. The PEEK material was ultrasonically cleaned with acetone, ethanol and distilled water for 10 min each, vacuum dried and then immersed in 72% nitric acid. The mixture was stirred and reacted at room temperature for 30 h. After the reaction was completed, the material was ultrasonically cleaned with distilled water until neutral and then vacuum dried to obtain the surface-nitrated polyether ether ketone material (named NP-3).

[0053] S4. Mix 2.0 g NP-3 with 0.30 g palladium on carbon and 12 mL hydrazine hydrate (85% by mass), and reflux at 105 °C for 7 h under nitrogen protection using 45 mL anhydrous ethanol as solvent. After the reaction, ultrasonically clean with ethanol and distilled water for 10 min each, and dry at 40 °C to obtain a polyetheretherketone material with amino groups on the surface (named AP-3).

[0054] S5. Place 2.0 g of AP-3 in a 2.5% (v / v) glutaraldehyde aqueous solution and soak at room temperature for 4 h. Then rinse thoroughly with deionized water 3 times to obtain glutaraldehyde-modified polyether ether ketone material (named GP-3).

[0055] S6. 2.0 g GP-3 and 10 mL of strontium-loaded self-assembled mineralized collagen solution were co-incubated at 4 °C for 12 h. After incubation, the mixture was gently rinsed with deionized water and then blocked with 0.70 mol / L glutamic acid solution for 2 h to obtain strontium-loaded polyetheretherketone composite material (named GP-SSMC-3).

[0056] Experimental testing: 1. The self-assembled mineralized collagen loaded with strontium ions obtained in Example 1 above was characterized by transmission scanning electron microscopy (TEM), such as... Figure 2 As shown. By Figure 2 The morphology of self-assembled mineralized collagen is visible, with strontium ion mineralization regions present within the collagen fibers. Detailed images of these mineralization regions are shown under magnification. Nanoparticles are encapsulated and confined within the intercellular spaces along the fiber axis, subsequently fusing and crystallizing to form self-assembled mineralized collagen. Its amorphous nature is confirmed by selected area electron diffraction (SAED).

[0057] In addition, XPS spectra were performed on the surface of the polyetheretherketone (PEEK) material samples obtained in each step of Example 1 above, and the results are as follows: Figure 3 As shown. By Figure 3 It can be seen that only C 1s and O 1s elements and a very small amount of N 1s element were detected on the untreated polyetheretherketone surface, while C 1s, N 1s and O 1s signals were present in all other groups. GP-SSMC detected Sr 3d signal at about 133.2 eV, confirming that the surface was doped with Sr element.

[0058] The surface hydrophilicity of the polyetheretherketone (PEEK) material samples obtained in each step of Example 1 was tested, and the results are as follows: Figure 4 As shown. By Figure 4It can be seen that the GP-SSMC obtained by the modification treatment in this embodiment has the strongest hydrophilicity. The wettability is improved after the material surface is modified with strontium ions, and the water contact angle decreases from 92.9° of PEEK to 55.8° of GP-SSMC. Under acidic conditions, it further decreases to 49.7°, confirming its pH responsiveness.

[0059] II. The strontium ion sustained-release capability of the strontium-loaded polyetheretherketone composite material (GP-SSMC) obtained in Example 1 was evaluated using inductively coupled plasma mass spectrometry (ICP-MS). The specific experimental steps for strontium ion sustained-release are as follows: GP-SSMC samples were immersed in 10 mL of phosphate-buffered saline (PBS) (0.01 M, pH 7.2) and incubated at 37°C with shaking at 100 rpm for 18 days. At predetermined time points, the supernatant was collected after centrifugation and replaced with an equal volume of fresh PBS to maintain sedimentation conditions. Sr was determined by ICP-MS. 2+ Concentration, each group should be repeated at least three times.

[0060] In addition, the strontium ion sustained-release curve of the strontium-loaded polyetheretherketone composite material obtained above is shown in the figure below. Figure 5 As shown. By Figure 5 It can be seen that the strontium-loaded polyetheretherketone composite material provided in this embodiment of the invention exhibits a pH-responsive interface, accelerating the release of strontium ions (Sr) under acidic conditions. 2+ Strontium ions are released continuously at a physiological pH of 7.4, while acidification increases both the release rate and the final cumulative concentration.

[0061] III. The cell viability of the polyether ether ketone material samples obtained through each step of Example 1 was evaluated by in vitro culture experiments using mouse mononuclear macrophages (Raw264.7).

[0062] Cell proliferation on the material surface was detected using the Cell Counting Kit (CCK-8, Beyotime, Shanghai, China); the specific procedure is as follows: 1. Place the samples sterilized by 15K cobalt-60 irradiation into a 48-well culture plate, with a drop density of 1×10⁻⁶ per well. 4 cell / mL cell suspension.

[0063] 2. Place the cell culture plate in a cell culture incubator with 5% CO2 saturated humidity at 37°C and change the culture medium every 2-3 days.

[0064] 3. After 1, 4 and 7 days of cell culture, remove the original culture medium and add 200-400 μL of new culture medium containing 10% CCK-8 solution. After culturing the culture plate in an incubator for 1-4 hours, take 100 μL of culture medium from each well and put it into a 96-well plate.

[0065] 4. Use an ELISA reader (iMark, Bio-Rad, USA) to measure the absorbance of each well at a wavelength of 450 nm.

[0066] in, Figure 6 This is a comparison of the Raw264.7 cell proliferation experiment results of the polyetheretherketone (PEEK) material obtained before and after each step of the treatment in Example 1. The M2 medium + GP-SSMC group refers to the group co-cultured with GP-SSMC material in M2-polarized mouse mononuclear macrophage culture medium to evaluate the effect of the material on cell viability under early immune conditions. Figure 6 It can be seen that the cell proliferation on the surface of the strontium-loaded polyether ether ketone composite material (GP-SSMC) is significantly better than that of other groups under different culture conditions, indicating that GP-SSMC has good biological activity.

[0067] IV. The osteogenic properties of the polyetheretherketone (PEEK) materials obtained before and after the treatments described in Example 1 were evaluated using an in vitro culture experiment with rat bone marrow mesenchymal stem cells (rBMSCs). The expression of alkaline phosphatase (ALP) in the PEEK materials obtained after surface modification in Example 1 was detected using a BCIP / NBT alkaline phosphatase colorimetric kit (Beyotime, Shanghai, China) to assess their osteogenic integration capacity. The specific procedures are as follows: 1. Place the sterilized sample into a 48-well culture plate and add culture medium according to the national standard for extract preparation to prepare the extract.

[0068] 2. In a blank 48-well culture plate, add a drop of 2 × 10⁻⁶ drops per well. 4 Cell suspensions of 1 cell / mL were prepared, and cells were cultured in the corresponding extract for each group.

[0069] 3. Place the cell culture plate in a cell culture incubator with 5% CO2 saturated humidity and culture at 37°C. Change the extraction medium every 2-3 days. After each use of the extraction medium, fresh culture medium needs to be added again for extraction.

[0070] 4. After 7 days of cell culture, remove the culture medium, wash three times with PBS, and then add alkaline phosphatase chromogenic reagent according to the manufacturer's instructions for staining. After staining, wash three times with double-distilled water.

[0071] 5. Take pictures using a fluorescence microscope.

[0072] in, Figure 7 This is a comparison chart showing the expression results of alkaline phosphatase (ALP) in rBMSCs of polyetheretherketone materials before and after each step of the treatment in Example 1. Figure 7 The results showed that the ALP expression in the strontium-loaded polyetheretherketone composite material was significantly better than that in other groups, indicating that strontium loading can promote ALP expression. Cultured bone marrow mesenchymal stem cells (BMSCs) in a mixture of osteogenic induction medium and M2 macrophage conditioned medium (M2 medium + GP-SSMC) further enhanced osteogenic activity, which is likely attributed to the presence of anti-inflammatory signals (including IL-10) in the conditioned medium. These results suggest that GP-SSMC can promote M2 macrophage polarization and support osteogenic differentiation.

[0073] Based on the above-described preferred embodiments of the present invention, and through the foregoing description, those skilled in the art can make various changes and modifications without departing from the inventive concept. The technical scope of this invention is not limited to the contents of the specification.

Claims

1. A method for preparing a polyetheretherketone composite material loaded with strontium ions, characterized in that, Includes the following steps: In the presence of chitosan, strontium ions react with carbonate ions in a liquid phase system to obtain a chitosan-stable amorphous strontium carbonate nanocomposite solution. Specifically, this involves: dissolving chitosan in deionized water at a mass concentration of 1.0%–3.0%, then adjusting the pH to 2–5 to obtain a chitosan solution; preparing a strontium salt aqueous solution with a mass concentration of 8%–20%, and adding it dropwise to the chitosan solution under stirring; subsequently adding carbonate at a mass equivalent to 1%–4% of the strontium salt to obtain a chitosan-stable amorphous strontium carbonate nanocomposite solution; wherein the mass ratio of chitosan to strontium salt is (0.3–0.4):(0.9–1). An amorphous strontium carbonate nanocomposite solution was mixed with a collagen solution, and the self-assembly and mineralization of collagen were promoted by dialysis and pH adjustment to obtain a strontium-loaded self-assembled mineralized collagen solution. Specifically, the mixture consisted of: mixing the amorphous strontium carbonate nanocomposite solution and acid-dissolved collagen solution at a volume ratio of (2-4):1, then dialysis in a phosphate buffer solution, with the phosphate buffer solution being changed periodically until the pH value changed to 5.0-7.0, resulting in a mixed system; adding 0.5-1.5 mol / L alkaline solution to the mixed system to adjust the pH value to 7.0-8.0 to promote the conversion of amorphous minerals, and then dialysis in a HEPES buffer solution to obtain a strontium-loaded self-assembled mineralized collagen solution; wherein the collagen was type I collagen; and the volume of the HEPES buffer solution was 100%-300% of the volume of the mixed system. Polyether ether ketone (PEEK) material was used as the matrix material and subjected to surface nitration treatment to obtain a matrix material with nitro groups on the surface. The nitro groups in the matrix material with nitro groups on the surface are reduced to amino groups to obtain a matrix material with amino groups on the surface. Glutaraldehyde was used to activate a matrix material with amino groups on its surface to obtain a glutaraldehyde-modified matrix material. Glutaraldehyde-modified matrix material was co-incubated with a strontium-loaded self-assembled mineralized collagen solution to achieve covalent fixation, resulting in a strontium-loaded polyether ether ketone composite material; the composite material was then blocked with a glutamic acid solution at a concentration of 0.1–0.9 mol / L.

2. The method for preparing the strontium-loaded polyetheretherketone composite material according to claim 1, characterized in that, The chitosan is carboxymethyl chitosan; the strontium salt is strontium chloride hexahydrate; and the carbonate is sodium carbonate.

3. The method for preparing the strontium-loaded polyetheretherketone composite material according to claim 1, characterized in that, The steps of using polyetheretherketone (PEEK) material as a matrix material and performing surface nitration treatment to obtain a matrix material with nitro groups on the surface specifically include: The matrix material was ultrasonically cleaned sequentially with acetone, ethanol and distilled water, and then vacuum dried to obtain the pretreated matrix material. The pretreated matrix material is immersed in a concentrated nitric acid solution with a mass concentration of 60%~75% and stirred. Then, it is ultrasonically cleaned to remove residual nitric acid and then vacuum dried to obtain a matrix material with nitro groups on the surface.

4. The method for preparing the strontium-loaded polyetheretherketone composite material according to claim 1, characterized in that, The step of reducing nitro groups in a matrix material with nitro groups on its surface to amino groups to obtain a matrix material with amino groups on its surface specifically includes: A matrix material with nitro groups on its surface was mixed with palladium on carbon and hydrazine hydrate, and anhydrous ethanol was used as a solvent to prepare a reduction reaction system. The system was refluxed at 90-110°C under a protective atmosphere. The volume fraction of hydrazine hydrate in the reduction reaction system was 10%-30%. After the reaction was completed, the material was ultrasonically cleaned to remove unreacted substances and then dried to obtain a matrix material with amino groups on its surface.

5. The method for preparing the strontium-loaded polyetheretherketone composite material according to claim 1, characterized in that, The steps for activating a matrix material with amino groups on its surface using glutaraldehyde to obtain a glutaraldehyde-modified matrix material specifically include: The matrix material with amino groups on its surface is immersed in a glutaraldehyde aqueous solution with a volume fraction of 1% to 2.5% to activate the amino groups on the surface and introduce active aldehyde groups. It is then rinsed to remove unreacted glutaraldehyde, thus obtaining a glutaraldehyde-modified matrix material.

6. A strontium-loaded polyetheretherketone composite material prepared by any one of claims 1-5.

7. The use of a strontium-loaded polyetheretherketone composite material as described in claim 6 in the preparation of bone graft materials, and / or bone fixation materials, and / or bone repair materials.

Citation Information

Patent Citations

  • Preparation method for gelatin / hydroxyapatite composite coating

    CN106963984A

  • Preparation method of bionic mineralized collagen scaffold

    CN107929812A

  • Zinc ion loaded polyether-ether-ketone composite material as well as preparation method and application thereof

    CN114533963A

  • Surface treatment of poly(aryl ether ketone)s

    US20230250247A1